Krisis hutang: Pelajaran dari tahun 1980an untuk 1990an - Graciela L. Kaminsky; Alfredo Pereira (Universitas Islam Indonesia, 1998)
One of the salient characteristics of the 1980s is the growth collapse of the Latin American debtor countries. The debt-overhang literature claims that the debt crisis in the main reason for the growth collapse.